Hypoxemia in thoracoscopic lung resection surgery using a video double-lumen tube versus a conventional double-lumen tube: A propensity score-matched analysis - Wang, Wei; Gong, Zhihao; Zhao, Mingye; Zhang, Zuojing; Qiu, Yuwei; Jiang, Qiliang; Wu, Jingxiang (Frontiers in Surgery, 2023)
Background: Malposition of the double-lumen tubes (DLTs) may lead to hypoxemia during one-lung ventilation (OLV). Video double-lumen tubes (VDLTs) enable continuous observation of DLT position and avoid displacement. We aimed to investigate whether VDLTs could reduce the incidence of hypoxemia during OLV compared with conventional double-lumen tubes (cDLT) in thoracoscopic lung resection surgery. Methods: This was a retrospective cohort study. Adult patients who underwent elective thoracoscopic lung resection surgery and required VDLTs or cDLTs for OLV at Shanghai Chest Hospital from January 2019 to May 2021 were included. The primary outcome was the incidence of hypoxemia during OLV between VDLT and cDLT. Secondary outcomes included bronchoscopy use, the degree of PaO2 decline, and arterial blood gas indices. Results: A total of 1780 patients were finally analyzed in propensity score-matched cohorts (VDLT vs. cDLT 1:1 n = 890). The incidence of hypoxemia decreased from 6.5% (58/890) in cDLT group to 3.6% (32/890) in VDLT group (Relative Risk [RR]: 1.812, 95% CI: 1.19 - 2.76, p = 0.005). The use of bronchoscopy was reduced by 90% in VDLT group (VDLT 10.0% (89/890) vs. cDLT 100% (890/890), p<0.001). PaO2 after OLV was 221 [136.0 - 325.0] mmHg in cDLT group compared to 234 [159.7 - 336.2] mmHg in VDLT group, p = 0.003. The percentage of PaO2 decline was 41.4 [15.4 - 61.9] % in cDLT group, while it was 37.7 [8.7 - 55.9] % in the VDLT group, p < 0.001. In patients who suffered from hypoxemia, there were no significant differences in arterial blood gas indices or the percentage of PaO2 decline. Conclusions: VDLTs reduce the incidence of hypoxemia and the use of bronchoscopy during OLV compared with cDLTs. VDLT may be a feasible option for thoracoscopic surgery.